Platelet Activation and Aggregation Induced by Recombinant von Willebrand Factors Reproducing Four Type 2B von Willebrand Disease Missense Mutations - de Romeuf, Christophe; Hilbert, Lysiane; Mazurier, Claudine (Thrombosis and Haemostasis, 1998)
Type 2B of von Willebrand disease (vWD) refers to qualitative variants with increased affinity of von Willebrand factor (vWF) for platelet glycoprotein Ib (GPIb). All the mutations responsible for type 2B vWD have been located in the A1 domain of vWF. In this study, various recombinant von Willebrand factors (rvWF) reproducing four type 2B vWD missense mutations were compared to wild-type rvWF (WT-rvWF) for their spontaneous binding to platelets and their capacity to induce platelet activation and aggregation. Our data show that the multimeric pattern of each mutated rvWF is similar to that of WT-rvWF but the extent of spontaneous binding and the capacity to induce platelet activation and aggregation are more important for the R543Q and V553M mutations than for the L697V and A698V mutations. Both the binding of mutated rvWFs to platelets and platelet aggregation induced by type 2B rvWFs are inhibited by monoclonal anti-GPIb and anti-vWF antibodies, inhibitors of vWF binding to platelets in the presence of ristocetin, as well as by aurin tricarboxylic acid. On the other hand, EDTA and a monoclonal antibody directed against GPIIb/IIIa only inhibit platelet aggregation. Furthermore, the incubation of type 2B rvWFs with platelets, under stirring conditions, results in the decrease in high molecular weight vWF multimers in solution, the extent of which appears correlated with that of plasma vWF from type 2B vWD patients harboring the corresponding missense mutation. This study supports that the binding of different mutated type 2B vWFs onto platelet GPIb induces various degrees of platelet activation and aggregation and thus suggests that the phenotypic heterogeneity of type 2B vWD may be related to the nature and/or location of the causative point mutation.